Kaitan Moral Disengagement dan Aggressive Driving Behavior : Tinjauan Pada Remaja Pengendara Sepeda motor - Juniarly, Amalia; Effendi, Efira Aflah (Personifikasi: Jurnal Ilmu Psikologi, 2022)
One of the factors of high traffic accidents is the growing rate of vehicles.  In Indonesia, traffic accidents that occur are dominated by two-wheeled vehicles, namely motorcycles and often involve young drivers. One of the causes of adolescent involvement in accidents is aggressive driving behavior which can be influenced by moral disengagement. This quantitative study aims to determine the role of moral disengagement on aggressive driving behavior in adolescent motorcyclists. The hypothesis of this research is that moral disengagement plays a role to aggressive driving behavior on adolescent motorcyclist. This research uses purposive sampling as a sampling technique. The respondents range from 14-19 year old motorcyclists in Palembang, amounting to about 150 respondents. The instrument used is the Aggressive Driving Behavior Scale (ADBS) by Houston et al. (2003) and the Moral Disengagement Scale by Bandura et al. (1996), both modified. Simple regression technique was used to analyze the research data and with the help of IBM SPSS 22. Based on the results of the regression analysis, the R square value between moral disengagement and aggressive driving behavior is 0.107, the F value is 17.682, and the significance value is 0.000 (p smaller than 0.005). This shows that moral disengagement has a significant role in aggressive driving behavior. Thus, the hypothesis proposed by this study can be accepted.